ЩОДО ФОРМУВАННЯ СУЧАСНОГО СПРИЙНЯТТЯ ПРАВ ЛЮДИНИ - Заросило, Володимир Олексійович (SUPREMANCE OF LAW, 2016)
The article deals with the separation of generations of human rights and their characteristics. It is noted that most scholars have identified four generations of human rights. However it is not always the generalization of the definition of certain human rights are correct. The proposal to qualify the types of human rights such as individual and collective, and that they are formed by certain rules were made